Spontaneous Background and Procedure-Related Microscopic Findings and Common Artifacts in Ocular Tissues of Laboratory Animals in Ocular Studies. (April 2021) - Sorden, Steven D.; Larsen, Thomas; McPherson, Leslie E.; Turner, Oliver C.; Carroll, Erica E.; Sharma, Alok K.
Identification of test article–related microscopic findings in ocular toxicology studies requires a working knowledge of the artifacts and procedure-related or background findings commonly encountered in such studies. The objective of this article is to provide a mini-atlas of the artifacts and procedure-related or spontaneous background findings commonly observed in ocular tissues from animals in toxicology studies of ocular drug candidates. Artifacts in the eye are often related to collection or fixation procedures and include swelling and vacuolation of lens fibers, separation of the neuroretina from the retinal pigment epithelium (RPE), and vacuolation of the optic nerve. Common in-life procedure-related findings include intravitreal injection needle tracks in the sclera and ciliary body pars plana and foci of RPE hypertrophy and/or hyperpigmentation at subretinal injection sites. Common background findings include corneal mineralization, uveal mononuclear cell infiltrates, and peripheral displacement of photoreceptor nuclei in the retina. A few uncommon spontaneous background findings that may be confused with test article–related findings, such as bilateral optic atrophy in macaques, are also included.